HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DAN DAYA LEDAK OTOT TUNGKAI TERHADAP KEMAMPUAN UNDER THE BASKET SHOOT PADA TIM BOLA BASKET PUTRI SMA NEGERI 3 PEKANBARU - Fauziah Fauziah; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study was conducted to determine whether there is a relationship between wrist flexibility and leg muscle explosive power on the shooting ability of the women's basketball team at SMA Negeri 3 Pekanbaru. The problem found in this research is that his under the basketball shoot ability has not shown satisfactory results, a player often fails to make a shot. This research was carried out in the field of SMAN 3 Pekanbaru. The population of this study were 12 female athletes of the basketball team at SMA Negeri 3 Pekanbaru. Based on the results of the study, the following conclusions can be drawn: There is a strong relationship between wrist flexibility and the results of the Under the basket stroke, where rtab is at a significant level  (0.05) = 0.602 meaning rcount (0.954)> rtab (0.602), there is a relationship strong leg muscle explosive power with results under a basket shoot, where rtab is at a significant level  (0.05) = 0.602 means rcount (0.959) <rtab (0.602) There is a jointly strong relationship between wrist flexibility and power Explosions of leg muscles with shots under the basket on the women's basketball team at SMA Negeri 3 Pekanbaru, where the household is at a significant level  (0.05) = 0.602 meaning Rhitung (0.969)> rtab (0.602).Key Words: Wrist Flexibility,Muscle Explosive power,Under The Basket Shoot